1996
DOI: 10.1042/bj3170925
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of β-adrenoceptor density and mRNA levels in the rat heart cell-line H9c2

Abstract: The regulation of the expression of beta-adrenoceptor (beta-ARs) is not thoroughly understood. We demonstrate that the rat heart cell-line H9c2 expresses both beta 1- and beta 2-ARs. In radioligand-binding experiments, the maximal binding capacity of (-)-[125I]-iodocyanopindolol was determined as 18 +/- 0.6 fmol/mg of protein with a KD of 35.4 +/- 4.1 pM. Competitive radioligand-binding experiments with subtype-specific beta-antagonists reveal a subtype ratio of beta 1- to beta 2-ARs of 29%: 71%. With competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 27 publications
6
18
0
Order By: Relevance
“…This cell line has shown electrophysiological and biochemical properties of both skeletal and cardiac tissues, including depolarization in response to acetylcholine and rapid activation of calcium currents through L-type channels. They have been used extensively in the literature as models for cardiomyoblasts and have been considered as a proper model to study molecular responses of the cardiomyocyte to oxidative damage [17,18]. Cells were grown in DMEM supplemented with 1.5 g l -1 sodium bicarbonate, 10% FBS, 100 U ml -1 of penicillin and 100 lg ml -1 of streptomycin in 75-cm 2 tissue culture flasks, and maintained at 37°C, in a humidified incubator containing 5% CO 2 .…”
Section: H9c2 Cell Culturementioning
confidence: 99%
“…This cell line has shown electrophysiological and biochemical properties of both skeletal and cardiac tissues, including depolarization in response to acetylcholine and rapid activation of calcium currents through L-type channels. They have been used extensively in the literature as models for cardiomyoblasts and have been considered as a proper model to study molecular responses of the cardiomyocyte to oxidative damage [17,18]. Cells were grown in DMEM supplemented with 1.5 g l -1 sodium bicarbonate, 10% FBS, 100 U ml -1 of penicillin and 100 lg ml -1 of streptomycin in 75-cm 2 tissue culture flasks, and maintained at 37°C, in a humidified incubator containing 5% CO 2 .…”
Section: H9c2 Cell Culturementioning
confidence: 99%
“…The H9c2 cardiomyocytes have characteristics of electrophysiological elements and signaling pathways of adult cardiomyocytes (12). This cell line provides a useful model for studying the interaction between ␤-AR and PI3K because in these cells, population of ␤-AR subtypes can be readily detected and PI3K has been shown to regulate their differentiation (9,19). We showed that ␤-AR stimulation-induced activation of PI3K is ␤ 2 -AR dependent.…”
Section: Discussionmentioning
confidence: 90%
“…In rat C6 glioma cells exposed to the agonist ISO, down-regulation of both subtypes occurs at similar rates (19,20), but when the cells are exposed to atypical agonists, only ␤ 2 AR levels are reduced (19). When rat H9c2 heart cells are treated with agonist, ␤ 2 AR but not ␤ 1 AR undergoes downregulation (21). Distinctions also are found in vivo.…”
mentioning
confidence: 86%